Pendampingan Caregiver Formal dalam Pengenalan Kondisi Gawat Darurat pada Lansia dan Penghitungan Early Warning System Score - Debora, Oda; Sulartri , Anastasia Sri; Diatanti, Narita (Kolaborasi: Jurnal Pengabdian Masyarakat, 2025)
Introduction: The old people who lives in nursing home received health care services, which is provided by formal caregivers. Most caregivers do not received health education about emergency, and therefore may not be able to recognize the signs and symptoms of emergencies in old people. When an emergency occurs, the assistance cannot be properly delivered and delay the referral decission. Objective: The purpose of this community service was to provide education about emergency in older people and improved ability to calculate Early Warning System Score (EWSS). Method: This public service was carried out by team form STIKes Panti Waluya Malang. This activity was conducted over three session. To increase caregiver knowledge, the community service team provided education through lecture and discussion. In order to improve caregiver’s skill, case based learning method was used to calculate EWSS score. Result: There was an increase in caregiver’s knowledge about 25%. Additionally, 86% caregivers were able to calculate and interpreted EWSS score. Conclusion: Providing education about older people emergency condition through lectures and discussion could improve caregiver’s knowledge. Furthermore, EWSS scoring can be applied in old people nursing home to provide objective assessment during referral.